2021
DOI: 10.1039/d0ta10494a
|View full text |Cite
|
Sign up to set email alerts
|

Defective Fe3GeTe2 monolayer as a promising electrocatalyst for spontaneous nitrogen reduction reaction

Abstract: The vital role of the spin polarization in the electrocatalytic N2 reduction reaction (eNRR) stimulates us to explore the potential of the newly discovered two-dimensional (2D) vdW ferromagnets materials as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…In a six-electron reduction reaction, the PDSs are usually the two intermediate steps: N 2 + H + + e – → *NNH and *NH 2 + H + + e – → *NH 3 . Additionally, the Δ G of the first and last hydrogenation steps should be as low as possible to guarantee low energy cost, e.g., Δ G *N2H – Δ G *N2 and Δ G *NH3 – Δ G *NH2 are lower than 0.5 eV for the best catalyst Ru . According to this criterion, Ti, V, Cr, Fe, Co, Ru, and Os are excluded (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…In a six-electron reduction reaction, the PDSs are usually the two intermediate steps: N 2 + H + + e – → *NNH and *NH 2 + H + + e – → *NH 3 . Additionally, the Δ G of the first and last hydrogenation steps should be as low as possible to guarantee low energy cost, e.g., Δ G *N2H – Δ G *N2 and Δ G *NH3 – Δ G *NH2 are lower than 0.5 eV for the best catalyst Ru . According to this criterion, Ti, V, Cr, Fe, Co, Ru, and Os are excluded (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…As we all know, there usually exist surface vacancies in the CVD-grown 2D materials, and the defective regions are usually chemically active and proved to enhance the interaction between the gas molecules and the substrate. 44,61,62 Qian et al 63 reported that the surface N-defective MSN is much more stable than that of inner N vacancy and surface Si vacancy, and the d-MSN is also proved to be thermodynamically stable via the ab initio molecular dynamics simulation. 58 Based on the above results, we further investigate the adsorption behavior of small molecules on the surface of N-defective MSN in this work.…”
Section: Adsorption Configurations and Adsorption Energiesmentioning
confidence: 99%
“…Based on Bader charge analysis, the charge change of the charge variations of Fe 2 C 1 N 2 along the preferred distal path was further investigated. According to previous studies, 36,65 the structure can be divided into three moieties (Fig. 5a), including the graphene substrate without the 2Fe + 2N unit (moiety 1), 2Fe + 2N unit (moiety 2) and the adsorbed N x H y (moiety 3).…”
Section: Paper Pccpmentioning
confidence: 99%
“…34,35 Furthermore, Fe is of high crustal abundance and the only common element of known nitrogenases for biological N 2 fixation, including FeFe, VFe, and MoFe. 36 With this in mind, Fe-based catalysts have become more popular for NRR catalysts' design in recent years. Huang et al theoretically reported that FeN 3 -embedded graphene was a promising catalyst for the NRR under mild conditions, in which Fe with high-spin polarization was regarded as an effective active site to adsorb and activate N 2 .…”
Section: Introductionmentioning
confidence: 99%